PRIMARY EDUCATION AND AESTHETIC SENSE TRAINING - Ziyayev A.N. (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
In this article, some issues of primary education and aesthetic sense education are analyzed. Proposals were developed on the basis of the conclusions drawn.